Download presentation

1
**Primitive Recursive Functions (Chapter 3)**

2
**Preliminaries: partial and total functions**

The domain of a partial function on set A contains the subset of A. The domain of a total function on set A contains the entire set A. A partial function f is called partially computable if there is some program that computes it. Another term for such functions partial recursive. Similarly, a function f is called computable if it is both total and partially computable. Another term for such function is recursive.

3
**Composition Let f : A → B and g : B → C g ͦ f : A → C**

Composition of f and g can then be expressed as: g ͦ f : A → C (g ͦ f)(x) = g(f(x)) h(x) = g(f(x)) NB: In general composition is not commutative: ( g ͦ f )(x) ≠ ( f ͦ g )(x)

4
Composition Definition: Let g be a function containing k variables and f1 ... fk be functions of n variables, so the composition of g and f is defined as: h(0) = k Base step h( x1, ... , xn) = g( f1(x1 ,..., xn), … , fk(x1 ,..., xn) ) Inductive step Example: h(x , y) = g( f1(x , y), f2(x , y), f3(x , y) ) h is obtained from g and f1... fk by composition. If g and f1...fk are (partially) computable, then h is (partially) computable. (Proof by construction)

5
Recursion From programming experience we know that recursion refers to a function calling upon itself within its own definition. Definition: Let g be a function containing k variables then h is obtained through recursion as follows: h(x1 , … , xn) = g( … , h(x1 , … , xn) ) Example: x + y f( x , 0 ) = x (1) f(x , y+1 ) = f( x , y ) + 1 (2) Input: f ( 3, 2 ) => f ( 3 , 1 ) + 1 => ( f ( 3 , 0 ) + 1 ) + 1 => ( ) + 1 => 5

6
**PRC: Initial functions**

Primitive Recursively Closed (PRC) class of functions. Initial functions: Example of a projection function: u2 ( x1 , x2 , x3 , x4 , x5 ) = x2 Definition: A class of total functions C is called PRC² class if: The initial functions belong to C. Function obtained from functions belonging to C by either composition or recursion belongs to C. s(x) = x + 1 n(x) = 0 ui (x1 , … , xn) = xi

7
**PRC: primitive recursive functions**

There exists a class of computable functions that is a PRC class. Definition: Function is considered primitive recursive if it can be obtained from initial functions and through finite number of composition and recursion steps. Theorem: A function is primitive recursive iff it belongs to the PRC class. (see proof in chapter 3) Corollary: Every primitive recursive function is computable.

8
**Primitive recursive functions: sum**

We have already seen the addition function, which can be rewritten in LRR as follows: sum( x, succ(y) ) => succ( sum( x , y)) ; sum( x , 0 ) => x ; Example: sum(succ(0),succ(succ(succ(0)))) => succ(sum(succ(0),succ(succ(0)))) => succ(succ(sum(succ(0),succ(0)))) => succ(succ(succ(sum(succ(0),0) => succ(succ(succ(succ(0))) => succ(succ(succ(1))) => succ(succ(2)) => succ(3) => 4 NB: To prove that a function is primitive recursive you need show that it can be obtained from the initial functions using only concatenation and recursion.

9
**Primitive recursive functions: multiplication**

h( x , 0 ) = 0 h( x , y + 1) = h( x , y ) + x In LRR this can be written as: mult(x,0) => 0 ; mult(x,succ(y)) => sum(mult(x,y),x) ; What would happen on the following input? mult(succ(succ(0)),succ(succ(0)))

10
**Primitive recursive functions: factorial**

0! = 1 ( x + 1 ) ! = x ! * s( x ) LRR implementation would be as follows: fact(0) => succ(null(0)) ; fact(succ(x)) => mult(fact(x),succ(x)) ; Output for the following? fact(succ(succ(null(0))))

11
**Primitive recursive functions: power and predecessor**

Power function In LRR the power function can be expressed as follows: pow(x,0) => succ(null(0)) ; pow(x,succ(y)) => mult(pow(x,y),x) ; Predecessor function In LRR the predecessor is as follows: pred(1) => 0 ; pred(succ(x)) => x ; p (0) = 0 p ( t + 1 ) = t

12
**Primitive recursive functions: ∸, | x – y | and α**

dotsub(x,x) => 0 ; dotsub(x,succ(y)) => pred(dotsub(x,y)) ; x ∸ 0 = x x ∸ ( t + 1) = p( x ∸ t ) What would be the output? dotsub(succ(succ(succ(0))),succ(0)) | x – y | = ( x ∸ y ) + ( y ∸ x ) abs(x,y) => sum(dotsub(x,y),dotsub(y,x)) ; α(x) = 1 ∸ x α(x) => dotsub(1,x) ; Output for the following? a(succ(succ(0))) a(null(0))

13
**Primitive recursive functions**

x + y f( x , 0 ) = x f( x , y + 1 ) = f( x , y ) + 1 x * y h( x , 0 ) = 0 h( x , y + 1 ) = h( x , y ) + x x! 0! = 1 ( x + 1 )! = x! * s(x) x^y x^0 = 1 x^( y + 1 ) = x^y * x p(x) p( 0 ) = 0 p( x + 1 ) = x x ∸ y if x ≥ y then x ∸ y = x – y; else x ∸ y = 0 x ∸ 0 = x x ∸ ( t + 1) = p( x ∸ t ) | x – y | | x – y | = ( x ∸ y ) + ( y ∸ x ) α(x) α(x) = 1 ∸ x

14
Bounded quantifiers Theorem: Let C be a PRC class. If f( t , x1 , … , xn) belongs to C then so do the functions g( y , x1 , ... , xn ) = f( t , x1 , …, xn ) g( y , x1 , ... , xn ) = f( t , x1 , …, xn )

15
Bounded quantifiers Theorem: Let C be a PRC class. If f( t , x1 , … , xn) belongs to C then so do the functions g( y , x1 , ... , xn ) = f( t , x1 , …, xn ) g( y , x1 , ... , xn ) = f( t , x1 , …, xn ) Theorem: If the predicate P( t, x1 , … , xn ) belongs to some PRC class C, then so do the predicates: ( t)≤y P(t, x1, … , xn ) (∃t)≤y P(t, x1, … , xn )

16
**Primitive recursive predicates**

x = y d( x , y ) = α( | x – y | ) x ≤ y α ( x ∸ y ) ~P α( P ) P & Q P * Q P v Q ~ ( ~P & ~Q ) y | x y | x = (∃t)≤x { y * t = x } Prime(x) Prime(x) = x > 1 & ( t)≤x { t = 1 v t = x v ~( t | x ) } Exercises for Chapter 3: page 62 Questions 3,4 and 5. Fibonacci function

17
**Bounded minimalization**

Let P(t, x1, … ,xn) be in some PRC class C and we can define a function g as follows:

18
**Bounded minimalization**

Let P(t, x1, … ,xn) be in some PRC class C and we can define a function g as follows: ,where

19
**Bounded minimalization**

Let P(t, x1, … ,xn) be in some PRC class C and we can define a function g as follows: ,where Function g also belongs to C as it is attained from composition of primitive recursive functions.

20
**Bounded minimalization**

Let P(t, x1, … ,xn) be in some PRC class C and we can define a function g as follows: ,where Function g also belongs to C as it is attained from composition of primitive recursive functions. t0 is the least value for for which the predicate P is true (1).

21
**Bounded minimalization**

Let P(t, x1, … ,xn) be in some PRC class C and we can define a function g as follows: ,where Function g also belongs to C as it is attained from composition of primitive recursive functions. t0 is the least value for for which the predicate P is true (1).

22
**Bounded minimalization**

Let P(t, x1, … ,xn) be in some PRC class C and we can define a function g as follows: ,where Function g also belongs to C as it is attained from composition of primitive recursive functions. t0 is the least value for for which the predicate P is true (1).

23
**Bounded minimalization**

Let P(t, x1, … ,xn) be in some PRC class C and we can define a function g as follows: ,where Function g also belongs to C as it is attained from composition of primitive recursive functions. t0 is the least value for for which the predicate P is true (1).

24
**Bounded minimalization**

Let P(t, x1, … ,xn) be in some PRC class C and we can define a function g as follows: ,where Function g also belongs to C as it is attained from composition of primitive recursive functions. t0 is the least value for for which the predicate P is true (1). g( y , x1 , ... , xn ) produces the least value for which P is true. Finally the definition for bounded minimalization can be given as:

25
**Bounded minimalization**

Let P(t, x1, … ,xn) be in some PRC class C and we can define a function g as follows: ,where Function g also belongs to C as it is attained from composition of primitive recursive functions. t0 is the least value for for which the predicate P is true (1). g( y , x1 , ... , xn ) produces the least value for which P is true. Finally the definition for bounded minimalization can be given as: Theorem: If P(t,x1, … ,xn) belongs to some PRC class C and there is function g that does the bounded minimalization for P, then f belongs to C.

26
**Unbounded minimalization**

Definition: y is the least value for which predicate P is true if it exists. If there is no value of y for which P is true, the unbounded minimalization is undefined.

27
**Unbounded minimalization**

Definition: y is the least value for which predicate P is true if it exists. If there is no value of y for which P is true, the unbounded minimalization is undefined. We can then define this as a non-total function in the following way:

28
**Unbounded minimalization**

Definition: y is the least value for which predicate P is true if it exists. If there is no value of y for which P is true, the unbounded minimalization is undefined. We can then define this as a non-total function in the following way: Theorem: If P(x1, … , xn, y) is a computable predicate and if then g is a partially computable function. (Proof by construction)

29
**Additional primitive recursive functions**

[ x / y ] , the whole part of the division i.e. [10/4]=2 R(x,y) , remainder of the division of x by y. pn , nth prime number i.e p1=2 , p2=3 etc.

30
Pairing functions Let us consider the following primitive recursive function that provides a coding for two numbers x and y.

31
Pairing functions Let us consider the following primitive recursive function that provides a coding for two numbers x and y. Example: <1,1> = 2 * ( ) ∸ 1 = 6 ∸ 1 = 5 <1,2> = 2 * ( 2*2 + 1) ∸ 1 = 10 ∸ 1 = 9

32
Pairing functions Let us consider the following primitive recursive function that provides a coding for two numbers x and y. Example: <1,1> = 2 * ( ) ∸ 1 = 6 ∸ 1 = 5 <1,2> = 2 * ( 2*2 + 1) ∸ 1 = 10 ∸ 1 = 9

33
Pairing functions Let us consider the following primitive recursive function that provides a coding for two numbers x and y. Example: <1,1> = 2 * ( ) ∸ 1 = 6 ∸ 1 = 5 <1,2> = 2 * ( 2*2 + 1) ∸ 1 = 10 ∸ 1 = 9 Define z to be as: < x , y > = z Then for any z there is always a unique solution x and y.

34
Pairing functions Let us consider the following primitive recursive function that provides a coding for two numbers x and y. Example: <1,1> = 2 * ( ) ∸ 1 = 6 ∸ 1 = 5 <1,2> = 2 * ( 2*2 + 1) ∸ 1 = 10 ∸ 1 = 9 Define z to be as: < x , y > = z Then for any z there is always a unique solution x and y.

35
Pairing functions Let us consider the following primitive recursive function that provides a coding for two numbers x and y. Example: <1,1> = 2 * ( ) ∸ 1 = 6 ∸ 1 = 5 <1,2> = 2 * ( 2*2 + 1) ∸ 1 = 10 ∸ 1 = 9 Define z to be as: < x , y > = z Then for any z there is always a unique solution x and y. Thus we have the solutions for x and y which can then be defined using the following functions:

36
**Pairing functions More formally this can written as:**

Pairing Function Theorem: functions <x,y>, l(z), r(z) have the following properties: are primitive recursive l(<x,y>) = x and r(<x,y>) = y < l(z) , r(z) > = z l(z) , r(z)≤ z

37
Gödel numbers Let (a1, … , an) be any sequence, then the Gödel number is computed as follows:

38
Gödel numbers Let (a1, … , an) be any sequence, then the Gödel number is computed as follows: Example: Take a sequence (1,2,3,4), the Gödel number will be computed as follows:

39
Gödel numbers Let (a1, … , an) be any sequence, then the Gödel number is computed as follows: Example: Take a sequence (1,2,3,4), the Gödel number will be computed as follows: Gödel numbering has a special uniqueness property: If [a1, … , an ] = [ b1, … , bn ] then ai = bi , where i = 1, … , n

40
Gödel numbers Let (a1, … , an) be any sequence, then the Gödel number is computed as follows: Example: Take a sequence (1,2,3,4), the Gödel number will be computed as follows: Gödel numbering has a special uniqueness property: If [a1, … , an ] = [ b1, … , bn ] then ai = bi , where i = 1, … , n Also notice: [ a1, … , an ] = [ a1, … , an, 0 ]

41
Gödel numbers Given that x = [a1, … , an ], we can now define two important functions:

42
Gödel numbers Given that x = [a1, … , an ], we can now define two important functions: Example: Let x = [ 4 , 3 , 2 , 1 ], then (x)2 = 3 and (x)4=1 and (x)0 = 0

43
Gödel numbers Given that x = [a1, … , an ], we can now define two important functions: Example: Let x = [ 4 , 3 , 2 , 1 ], then (x)2 = 3 and (x)4=1 and (x)0 = 0 Lt(10) = will be the length of the sequence derived using Gödel numbering

44
Gödel numbers Given that x = [a1, … , an ], we can now define two important functions: Example: Let x = [ 4 , 3 , 2 , 1 ], then (x)2 = 3 and (x)4=1 and (x)0 = 0 Lt(10) = will be the length of the sequence derived using Gödel numbering So: 10 = 2^1 * 3^0 * 5^1 = [ 1, 0, 1 ] => Lt(10) = 3

45
Gödel numbers Given that x = [a1, … , an ], we can now define two important functions: Example: Let x = [ 4 , 3 , 2 , 1 ], then (x)2 = 3 and (x)4=1 and (x)0 = 0 Lt(10) = will be the length of the sequence derived using Gödel numbering So: 10 = 2^1 * 3^0 * 5^1 = [ 1, 0, 1 ] => Lt(10) = 3 Sequence Number Theorem: (1)

46
Gödel numbers Given that x = [a1, … , an ], we can now define two important functions: Example: Let x = [ 4 , 3 , 2 , 1 ], then (x)2 = 3 and (x)4=1 and (x)0 = 0 Lt(10) = will be the length of the sequence derived using Gödel numbering So: 10 = 2^1 * 3^0 * 5^1 = [ 1, 0, 1 ] => Lt(10) = 3 Sequence Number Theorem: (1) (2)

Similar presentations

OK

1 A Single Final State for Finite Accepters. 2 Observation Any Finite Accepter (NFA or DFA) can be converted to an equivalent NFA with a single final.

1 A Single Final State for Finite Accepters. 2 Observation Any Finite Accepter (NFA or DFA) can be converted to an equivalent NFA with a single final.

© 2018 SlidePlayer.com Inc.

All rights reserved.

Ads by Google

Ppt on etiquette and manners in office Ppt on holographic technology schools Ppt on disaster recovery plan Ppt on how to use powerpoint 2013 Download maths ppt on number system for class 9 Ppt on latest technology in electrical Download ppt on oxidation and reduction chemistry Ppt on construction for class 10 cbse Ppt on various categories of software Ppt on cloud computing in ieee format